Le jusnaturalisme en Europe et en outre-mer : Antonio Vieira face au droit naturel et à l’esclavage des Indiens de São Paulo (1694) - Antônio David; Carlos Zeron (Clio@Themis, 2022)
Although it is a commonplace to say that, in the first modernity, the debate between theologians, philosophers and jurists found in jusnaturalism one of its high moments, the decisive role of the American experience in the elaboration of the concepts that informed it is not always recognized. Navigating between the Old and the New World, Antônio Vieira engaged in an original way in this debate, when dealing with problems related to colonial administration in Brazil and indigenous captivity.